POTENCY OF BLUE CARBON ON SEAGRASS (Cymodocea serrulata) IN SEAWATER OF PONCAN ISLAND SIBOLGA NORTH SUMATERA PROVINCE - Indrawan Ade Putra; Thamrin '; Zulkifli ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The rapid growth of industrial sectors in various countries leads to an increase in greenhouse gas emissions (global warming) such as carbon dioxide (CO2) in the atmosphere. One important aspect of reducing carbon gas is the maintenance of forests and oceans to store carbon. One of the potential marine resources as blue carbon is seagrass beds. Development of Poncan Island into a marine tourism area estimated will endanger the existence of seagrass vegetation that makes marine ecosystems as blue carbon is reduced, one of them which is Cymodocea serrulata. The research was conducted in March-May 2017 in the seawater of Poncan Island, Sibolga, which aims to determine the content of biomass, average of C-organic, and find parts of seagrass as the largest blue carbon. Sampling using a quadratic transect method performed at 3 station. The results show that the largest biomass and blue carbon of all research sites located in the Below Ground section (roots and rhizomes) with value is 27,57 gbk/m2 and 6,13 gC/m2. The highest average C-organic content in all research sites located in the root of the seagrass with value is 24,17%.Keywords: Global Warming, Seagrass, Biomass, C-organic, Blue Carbon, Poncan Island